Seasonal Trends in Heavy Metal Pollution and Water Quality in the Chashma (Indus River, Pakistan): A Study on Environmental Health Risks - Naz, Saira; Habib, Syed Sikandar; Arshad, Madeeha; Majeed, Saima; Mohany, Mohamed (Water, air, and soil pollution, 2025)
Heavy metal contamination in aquatic ecosystems poses a significant environmental threat, particularly in river systems subject to seasonal variation. This study examined the seasonal dynamics of five heavy metals such as lead (Pb), zinc (Zn), copper (Cu), chromium (Cr) and cadmium (Cd) in water, sediment, and the muscle tissue of Cyprinus carpio collected from the Chashma Barrage on the Indus River, Pakistan. In parallel, key water quality parameters including temperature, pH, and dissolved oxygen (DO) were monitored across four seasons to evaluate their impact on metal mobility and bioaccumulation. The results showed pronounced seasonal fluctuations, with summer characterized by the highest water temperature (38.22 °C) and lowest DO levels (4.72 mg/L), conditions that promote metal solubility and biological uptake. Concentrations of Pb and Cd in fish muscle peaked during the summer, while sediments also exhibited elevated metal levels during periods of increased runoff. Statistical analyses, including correlation and cluster methods, revealed strong associations between water quality variables and metal distribution. These findings underscore the role of seasonal environmental changes in influencing contaminant behavior and highlight the importance of continuous monitoring and targeted regulatory strategies to mitigate heavy metal pollution, protect freshwater biodiversity and ensure public health. Graphical Abstract